COVID-19 und die Niere - Rohn, H. (Gastroenterologe, 2020)
The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic has become one of the greatest global challenges of our time. It quickly became clear that coronavirus disease 2019 (COVID-19) affects not only the lungs but also other organs to varying degrees. The kidneys are particularly frequently affected. Many patients without underlying kidney diseases already show urinary abnormalities at the onset of COVID-19 and often run the risk of developing acute kidney injury.